Automated People Movers and Automated Transit Systems 2016 : innovation in a rapidly urbanizing world : proceedings of the 15th International Conference, April 17-20, 2016, Toronto, Ontario, Canada - Sproule, William J., 1948- (American Society of Civil Engineers, 2016)
"This collection contains 27 peer-reviewed papers that cover a broad range of subjects within the automated people movers (APMs) and automated transit systems (ATSs) industry. Topics include: airport projects and other major activity centers; automated train control; personal rapid transit; facility planning and design; system improvement, safety, and security; and standards and policy. Transportation engineers, builders, designers, planners, owners, and operators of automated transit in all forms will find these papers of interest."-- ASCE website
"The 15th International Conference on Automated People Movers and Automated Transit Systems"--Page iii
Sponsored by The Transportation & Development Institute (T & DI) of the American Society of Civil Engineers.
Keywords: Local transit -- Congresses.; Railroads, Local and light -- Congresses.; Transportation -- Passenger traffic -- Congresses.; elektronické knihy; electronic books